Empowering Orphans Through Qur’anic Values And The ACTORS Framework In The Indonesian Context - Rifqi As’adah; Abad Badruzaman; Salamah Noorhidayati; Sofwan AlJauhari (Pondok pesantren As-salafiyah As-Safi'iyyah, 2027)
Orphan empowerment remains one of the most urgent moral and social imperatives in Muslim-majority societies, especially in Indonesia, where the COVID-19 pandemic has intensified poverty and social inequality. Orphans experience complex, interrelated challenges, including economic deprivation, educational exclusion, emotional vulnerability, and limited access to healthcare and legal protection. This study explores Qur’anic perspectives on orphans and reinterprets their ethical and spiritual dimensions through the ACTORS framework Authority, Confidence and Competence, Trust, Opportunity, Responsibility, and Support as an integrative model of empowerment. Employing a qualitative design with a library-based approach and the tafsir maudhu‘i (thematic exegesis) method, the research collects and categorizes Qur’anic verses on orphans, analyses their moral implications, and contextualizes them within Indonesia’s socio-cultural environment. The findings reveal that the Qur’an envisions empowerment not solely as the provision of material assistance but as a holistic process combining spiritual formation, social justice, and structural inclusion. The ACTORS framework functions as an interpretive bridge linking divine revelation with contemporary empowerment theories, highlighting shared values of trust, competence, accountability, and compassion. The study concludes that effective orphan empowerment in Indonesia requires a synergistic partnership among governmental bodies, religious institutions, and civil society organizations. Such cooperation is essential to ensure inclusive, sustainable, and faith-based social transformation that nurtures orphans not as passive recipients of charity but as active contributors to personal and communal development.